1997
DOI: 10.1557/proc-480-187
|View full text |Cite
|
Sign up to set email alerts
|

Combined Tripod Polishing and Fib Method for Preparing Semiconductor Plan View Specimens

Abstract: Combining substantial pre-thinning of semiconductor device specimens via tripod polishing, followed by multiple, selective material removal steps with a focussed ion beam (FIB) tool, offers some unique possibilities with regard to preparing plan-view specimens at precise locations in the material below, and in the interconnect layers above, the semiconductor surface. Extension of these methods to other types of specimens in different configurations allows for the fabrication of multiple specimens on the same T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…3,10,11 Reducing the thickness of the initial piece of material to only 2-3 mm or less in the volume of interest offers several advantages, such as reduced FIB milling time and a reduced fluorescence yield contribution from the neighboring material in analytical TEM investigations with energy-dispersive x-ray analysis (EDX). A modified version of this technique can also be used to prepare planview specimens.…”
Section: Methods Requiring Pre-thinningmentioning
confidence: 99%
“…3,10,11 Reducing the thickness of the initial piece of material to only 2-3 mm or less in the volume of interest offers several advantages, such as reduced FIB milling time and a reduced fluorescence yield contribution from the neighboring material in analytical TEM investigations with energy-dispersive x-ray analysis (EDX). A modified version of this technique can also be used to prepare planview specimens.…”
Section: Methods Requiring Pre-thinningmentioning
confidence: 99%
“…Since our results have shown that the epoxy can penetrate to a depth of about10 µ m or more, the sample would need to be FIB cut using the cleaning cross sectioning to a total thickness of 16–20 µ m. The epoxy would need to be removed from both cross sectional surfaces with the FIB, as described above, and then oriented 90º. A lift-out procedure could then be used to remove the thinned plan view section at the desired depth for further thinning to electron transparency (Anderson & Klepis, 1997). The flexibility of this sample preparation procedure in terms of sample geometry makes it useful for TEM preparation of a variety of samples, including ballistic fragments and multiphase materials or composites with specific directionalities.…”
Section: Discussionmentioning
confidence: 99%
“…2. Both sides of the small specimen are then carefully polished using a "tripod polisher" (Anderson et al, 1997) in order to produce parallel surfaces and minimize the mechanical damage introduced during diamond saw cutting. The polished sample should have a thickness of less than 100 µm.…”
Section: Conventional H-bar Techniquementioning
confidence: 99%